2021
DOI: 10.1007/s12630-020-01903-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes in those consuming medical cannabis: a prospective longitudinal observational study in chronic pain patients

Abstract: Purpose We investigated patients with chronic pain seeking medical cannabis. We assessed their demographics, patterns of cannabis use, and the longterm effectiveness of cannabis on their pain and functional domains. Methods This observational study enrolled patients between 8 September 2015 and 31 July 2018 from community-based cannabis clinics in Ontario, Canada. In addition to collecting demographic information, the primary outcomes studied were pain intensity and painrelated interference scores assessed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
22
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 36 publications
10
22
1
4
Order By: Relevance
“…The recent article by Meng et al presents an interesting and courageous longitudinal investigation on the administration of cannabis extracts for the management of chronic pain. 1 The authors discuss study limitations, and we agree with the points made. Yet, the lack of welldefined good manufacturing practice certifications for the cannabis extracts used throughout the investigation could in part explain the administration of cannabis reported high participant attrition/low completion rate, of 25% at 12 months.…”
Section: To the Editorsupporting
confidence: 67%
See 1 more Smart Citation
“…The recent article by Meng et al presents an interesting and courageous longitudinal investigation on the administration of cannabis extracts for the management of chronic pain. 1 The authors discuss study limitations, and we agree with the points made. Yet, the lack of welldefined good manufacturing practice certifications for the cannabis extracts used throughout the investigation could in part explain the administration of cannabis reported high participant attrition/low completion rate, of 25% at 12 months.…”
Section: To the Editorsupporting
confidence: 67%
“…Other than the fact that different amounts of cannabis extract were self-reported, it is not known what cannabis molecules patients were consuming in the study by Meng et al 1 Quantities ranging from \ 1 g to [ 20 g, predominantly from dried cannabis extracts or extracts in oil, were the most common forms used. Formulations of cannabis-based medicines that improve chronic pain must include consistent well-defined and specific levels of D9THC and CBD-a notion supported by the published literature and systematic reviews.…”
Section: To the Editormentioning
confidence: 99%
“…In addition to accumulating evidence of cannabis’ therapeutic value across many conditions that are common in this population ( Babson et al, 2017 ; Bhattacharyya et al, 2018 ; Gibson et al, 2021 ; Jensen et al, 2015 ), there is also increasing recognition of its harm reduction potential ( Lucas, 2017 ). Evidence suggests cannabis use reduces the use of drugs like opioids and benzodiazepines ( Meng et al, 2021 ; Purcell et al, 2019 ). However, the cost of cannabis treatments must also be covered through public drug insurance if socioeconomically marginalized populations are to receive these medical or harm reduction benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The favourable response to oil-based cannabis may be due to the slower onset of the effect compared with smoking cannabis, as well as easier dose titration. Despite this interesting result, the authors highlighted that depression scores increased during the study [ 287 ]. Although the results are not conclusive, it is important to underline that further studies have shown that cannabis may have negative effects on the mental health of treated patients [ 288 , 289 ], and that it may exacerbate neurological diseases such as epilepsy and anxiety [ 289 ].…”
Section: Discussionmentioning
confidence: 99%